2018
DOI: 10.1186/s12885-018-4219-7
|View full text |Cite
|
Sign up to set email alerts
|

From symptom discovery to treatment - women's pathways to breast cancer care: a cross-sectional study

Abstract: BackgroundTypically, women in South Africa (SA) are diagnosed with breast cancer when they self-present with symptoms to health facilities. The aim of this study was to determine the pathway that women follow to breast cancer care and factors associated with this journey.MethodsA cross-sectional study was conducted at a tertiary hospital in the Western Cape Province, SA, between May 2015 and May 2016. Newly diagnosed breast cancer patients were interviewed to determine their socio-demographic profile; knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 33 publications
10
95
3
Order By: Relevance
“…Raising satisfaction derived in the hospital for treatment of other minor illnesses might build confidence and enduring relationship between potential breast cancer patients and the clinicians. 16 and then in a subsequent study of 201 patients; they reported a higher proportion of long delays in the system's interval 24 . Roy et al 25 in Bangladesh and Maghous et al 26 in Morocco, both reported that doctors were complicit in a third of long interval situations 25,26 .…”
Section: Discussionmentioning
confidence: 90%
“…Raising satisfaction derived in the hospital for treatment of other minor illnesses might build confidence and enduring relationship between potential breast cancer patients and the clinicians. 16 and then in a subsequent study of 201 patients; they reported a higher proportion of long delays in the system's interval 24 . Roy et al 25 in Bangladesh and Maghous et al 26 in Morocco, both reported that doctors were complicit in a third of long interval situations 25,26 .…”
Section: Discussionmentioning
confidence: 90%
“…Harirchi in Tehran 23 and Yau et al in Hong Kong 24 reported a higher proportion of patients with help-seeking delay. Moodley et al rst reported a higher proportion of delay in the patient interval among 20 patients in South Africa 16 and then in a subsequent study of 201 patients; they reported a higher proportion of long delays in the system's interval 25 . Roy et al 26 in Bangladesh and Maghous et al 27 in Morocco, both reported that doctors were complicit in a third of long interval situations 26,27 .…”
Section: Discussionmentioning
confidence: 97%
“…Length of diagnosis has been found to be associated with number of hospitals visited (Shieh et al, 2014). Study by Moodley et al, (2018) also showed that 40% of women had visited 4 or more health care visits from the time of first symptom discovery and definitive breast cancer diagnosis. Other reasons for the delay in seeking diagnosis and treatment was affordability and not suspected for the breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated to look at the sufficiency of the estimated parameter with the desired precision based on the study conducted by Moodley et al, (2018) where the overall median time from the symptom discovery to initiation of treatment was 110 days. Considering a 5% alpha error and a relative precision of 7.3%, the study required a minimum sample of 180 subjects.…”
Section: Methodsmentioning
confidence: 99%